Improved Mg Dopant Activation in p‐GaN and Enhanced Electroluminescence in InGaN/GaN LEDs by Plasma Immersion Ion Implantation of Phosphorus. Issue 18 (25th June 2018) - Upadhyay, Pankaj; Saha, Dipankar
Abstract : In this study, the authors demonstrate improved p‐type Mg dopant activation near surface by P ion implantation, which otherwise remain inactive due to a combination of self compensation, formation of Mg‐H complexes and high activation energy. The improvement is mainly attributed to the reduction in self‐compensation by a reduction in N vacancies near the surface and potential formation of by‐products suppressing Mg‐H complexes. In addition, inclusion of P by plasma‐immersion ion implantation creates a non‐uniform dopant activation leading to a built‐in electric field which further assists in ionizing the Mg dopants. The near‐surface improved p‐ dopant activation is manifested as a reduction in the contact resistance and specific contact resistivity. The contact resistance and specific contact resistivity are found to decrease by 68.7 and 77.4%, respectively, for P implanted p‐GaN samples in comparison to that of the control samples. The enhanced p‐doping is found to increase electro‐luminescence intensity by 264% for P implanted p‐top electrically injected light emitting diodes. The improved p‐type properties for GaN may find potential applications in the realization of electrically injected high efficiency optoelectronic devices. Abstract : The work demonstrates enhanced Mg activation and improved p‐doping in GaN when co‐doped with P. The improvement is attributed to a reduction in N‐vacancy and suppression of Mg‐H complex. The contact resistance and specific‐contact‐resistivity on p‐GaN reduce by 68 and 77%, respectively. The improved hole concentration is found to increase the performance of a LED by more than 200%.